Association of OPRK1 gene polymorphisms with opioid dependence in addicted men undergoing methadone treatment in an Iranian population. Issue 4 (2nd October 2017) - Albonaim, Ali; Fazel, Hedyeh; Sharafshah, Alireza; Omarmeli, Vahid; Rezaei, Sajjad; Ajamian, Farzam; Keshavarz, Parvaneh
ABSTRACT: Previous studies have shown significant associations between OPRK1 and susceptibility to opioid dependence and the relationships between libido dysfunction and insomnia among opium addicts who underwent methadone maintenance treatment. The authors investigated the single locus and haplotype association of rs997917, rs6985606, and rs6473797 with susceptibility to opioid addiction. Samples were selected among 202 healthy individuals and 202 opium addicts undergoing methadone maintenance treatment. Genomic DNA was extracted from the whole blood samples of all subjects through a salting out procedure. All three variants were genotyped in the studied subjects using Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR). The whole analysis process was performed using SNPAlyze and SPSS ver.20 software packages. According to the single locus analyses, rs997917 and rs6985606 represented significant associations with opium addiction under recessive ( p = 0.0128) and co-dominant ( p = 0.0001) inheritance models, respectively. The haplotypes C-T-C (Permutation p = 0.014) and C-T-T (Permutation p = 0.0002) were significantly associated with opioid dependence. Among methadone maintenance treatment individuals, rs997917 was significantly associated with insomnia in both allelic and genotypic levels ( p = 0.0001 and p = 0.038, respectively). Furthermore, rs6985606 had the only significant association with the co-incidence of insomnia and libido dysfunction in the methadone maintenance treatment group ( p = 0.038). The OPRK1 gene variants showed significant association with susceptibility to opioid dependence among Iranians.